Prognostic Impact of AJCC/UICC 8th Edition New Staging Rules in Oropharyngeal Squamous Cell Carcinoma - Würdemann, Nora; Wagner, Steffen; Sharma, Shachi Jenny; Prigge, Elena-Sophie; Reuschenbach, Miriam; Gattenlöhner, Stefan; Klussmann, Jens Peter; Wittekindt, Claus (Frontiers in Oncology, 2017)
Introduction: The purpose of this study was to test whether the 8th edition of the AJCC/UICC TNM staging system (UICC) precisely differentiates between stages and reflects disease outcome in Human Papilloma Virus (HPV)-associated Oropharyngeal squamous cell carcinoma (OPSCC). Patients and methods: OPSCC patients that were diagnosed between 2000 and 2016 were included in this analysis and HPV-status was determined by combined DNA- and p16-testing. Stratification was done according to 7th and 8th UICC staging rules. Incidence trends of HPV-associated tumorigenesis, 5-year overall survival (OS) according to tumor stages as well as the influence of therapy and risk factors towards the outcome were calculated using Kaplan–Meier method and Cox proportional-hazards model. Results: A significant increase (2000; n=8/39 (21%)- 2015; n=17/32 (53%); p=0.002) in HPV-associated OPSCC was seen in the observation period. Together, 150/599 (25.0%) of the patients had HPV driven OPSCC and 64.7% of curative treatments in all OPSCC patients included upfront surgery of the primary and the neck. 7th edition staging rules led to no discrimination in all respective four UICC stages in HPV OPSCC underlining the need for new staging rules. However, only discrimination between stages I vs. II and III vs. IV was significant in our patients with HPV-OPSCC (94.4% vs. 77.5%; p=0.031 and 63.9% vs, 25.0%; p=0.013), and stages II vs. III did not differ in OS rates (p=0.257), when applying the new staging rules. For HPV negative OPSCC significant outcome differences were only seen between UICC stages III vs. IV (57.6% vs. 35.2%; p=0.012). Discussion: While the 7th edition of UICC shows invalid discrimination between stages, 8th edition is more suitable for HPV-associated carcinoma. Due to lack of differentiation between stages II and III further adaption is essential.